Structure and bioactivity of a polysaccharide containing uronic acid from Polyporus umbellatus sclerotia. (5th November 2016) - He, Pengfei; Zhang, Anqiang; Zhang, Fuming; Linhardt, Robert J.; Sun, Peilong
Highlights: A novel polysaccharide (PUP80S1) was obtained from Polyporus umbellatus sclerotia. Structure characterization of PUP80S1 containing uronic acid was elucidated by NMR. Globular chain conformation of PUP80S1 was determined by Atomic force microscopy. Antioxidant activity of two polysaccharides having similar structure were compared. Abstract: Polyporus umbellatus is a medicinal fungus, has been used in traditional Chinese medicine for thousands years for treatment of edema, scanty urine, vaginal discharge, jaundice and diarrhea. The structure of a soluble polysaccharide (named PUP80S1), purified from the sclerotia of Polyporus umbellatus was elucidated by gas chromatography (GC), GC–mass spectrometry and nuclear magnetic resonance spectroscopy. PUP80S1 is a branched polysaccharide containing approximately 8.5% uronic acid and having an average molecular weight of 8.8 kDa. Atomic force microscopy of PUP80S1 reveals a globular chain conformation in water. Antioxidant tests, Oxygen radical absorption capacity and 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assays indicate that PUP80S1 possesses significant antioxidant activity. But the related polysaccharide, PUP60S2, which contains more uronic acid residues and a higher level of branching, shows better antioxidant activity. These results suggest that structure features of polysaccharides play an important role in their physiological functions.